Improving Quality of Life in Hemodialysis Patients with Intradialysis Hypertension Using “SEHAT” Nursing Interventions - Yunie Armiyati; Suharyo Hadisaputro; Shofa Chasani; Untung Sujianto (Media Keperawatan Indonesia, 2021)
Intradialytic hypertension can reduce the quality of life in hemodialysis patients. Providing appropriate nursing interventions will reduce morbidity, and improve the quality of intradialytic hypertensive patients. Provision of “SEHAT” nursing intervention package in the form of providing support, education and empowering, holistically with attention to therapeutic sensitivity can be applied to overcome patients problems. The purpose of the study was to analyze the "SEHAT" nursing intervention package to improve the quality of life of intradialytic hypertensive patients. The research method was a randomized controlled trial on 40 samples of hemodialysis patients which were divided into 20 group samples and 20 control group samples. The research instrument uses the Indonesian version of the Kidney Disease Quality of Life (KDQOL-36). The intervention was carried out for 4 weeks using the SEHAT nursing intervention package. The results showed an increase in the quality of life scores of respondents in the intervention group after being given SEHAT nursing intervention (p=0.000). There was a significant difference in the quality of life scores between the intervention group and the control group after being given the intervention (p=0.000). The “SEHAT” nursing intervention package is effective for improving the quality of life of intradialytic hypertensive patients.